Design of rectenna with improved RF-TO-DC power conversion efficiency for RF energy harvesting - Meor Said, Maizatul Alice (2018)
This thesis presents novel techniques for the design of rectenna for RF energy harvesting which allow for the realization of wireless microwave energy transfer. Energy harvesting is a rapidly growing area in many scientific and engineering related fields due to the need for finding solutions to the world’s power issues. Based on the previous works, there are many limitations and drawbacks exists in currently used technique such as low RF-to-DC power conversion efficiency or increase in the number of antenna elements enlarges the overall aperture size of the rectenna, the resulting devices are large and more difficult to install which limits the potential of further enhancement in the conversion efficiency. Therefore, the overall objective of this research work is to develop an effective rectenna for RF energy harvesting system. These rectenna have an advantage of high gain and high efficiency properties which optimized the overall rectenna performance. All the rectenna designs were developed based on stacked air-gap rectenna technology by integrating the rectifying circuit with the high gain antenna. In order to validate the concept, all rectenna designs were manufactured and measured. The experimental results show excellent agreement with the simulated performance. Both antennas and rectifiers have been designed by using Computer Simulation Technology (CST) and Advance Design System (ADS) respectively. A low cost 4.6 permittivity FR4 substrate has been used in the fabrication process. For rectifier, the highest output voltage that can be achieved is 14.52 V when the input power is at 30 dBm. On the other hand, the most optimized antenna amongs all can achieved gain of 9.01 dB and return loss of more than -22 dB. The highest measured RF-to-DC conversion efficiency of the optimized rectenna design is 85% when the input power is 20 dBm applied to the circuit. The main benefit of the rectenna designs are high gain, high RF to DC power conversion efficiency, high DC output voltage as well as being able to easily integrate with other planar devices at a low cost and using standard printed circuit board process. This new class of rectenna is considered suitable for applications, particularly where the gain can be tolerated and the RF-to-DC power conversion efficiency is very important, such as in the case of agriculture and health sensors of wireless sensor network